Community-based organizations and mainstream educational change: Dynamics and Dilemmas - Ronald Podeschi (Adult Education Research Conference, 1995)
Based on a decade of working with a Southeast Asian refugee organization, this analysis attempts to sort out useful working ideas and perspectives for professionals involved in change efforts at educational institutions through community-based organizations.